Nemopsis mianzani n. sp. (Hydrozoa, Bougainvilliidae), a new hydromedusa from central Chile - Oliveira, Otto M. P.; Feliú, Guillermo; Palma, Sergio (Zootaxa, 2015)
The genus Nemopsis, a bougainvillid hydrozoan with a dominant medusa phase, currently includes three species (Nemopsis bachei, N. dofleini and N. hexacanalis), all characterized by the presence of a pair of club-shaped tentacles in the median portion of the marginal bulbs. In this paper, we describe a fourth species, based on the medusa collected off Dichato, central Chilean coast.